2014
DOI: 10.1248/bpb.b14-00163
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Extracts from <i>Punica granatum</i> and <i>Terminalia chebula</i> Are Anti-inflammatory and Increase the Survival Rate of Chickens Challenged with <i>Escherichia coli</i>

Abstract: Avian pathogenic Escherichia coli (APEC) causes inflammation in multiple organs of chickens called avian colibacillosis, and results in serious economic loss to the chicken industry. Polyphenolic compounds possess a wide range of physiological activities that may contribute to their beneficial effects against inflammation-related diseases. In this study, the curative effect and mechanism of action of the polyphenolic extracts from Punica granatum L. and Terminalia chebula RETZ. in chickens challenged with APEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The findings suggest that CT supplementation can ameliorate the intestinal inflammatory response induced by heat stress. A previous study reported that polyphenolic extracts from Punica granatum and Terminalia chebula reduced the mRNA expression of various pro‐inflammatory cytokines, including IL‐1β, IL‐8 and TNF‐α, in the ileum of broilers challenged with Escherichia coli (Zhong et al., ). Polyphenol‐rich extracts of grape and hops were also reported to be anti‐inflammatory in the intestinal mucosa of pigs (Fiesel, Gessner, Most, & Eder, ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that CT supplementation can ameliorate the intestinal inflammatory response induced by heat stress. A previous study reported that polyphenolic extracts from Punica granatum and Terminalia chebula reduced the mRNA expression of various pro‐inflammatory cytokines, including IL‐1β, IL‐8 and TNF‐α, in the ileum of broilers challenged with Escherichia coli (Zhong et al., ). Polyphenol‐rich extracts of grape and hops were also reported to be anti‐inflammatory in the intestinal mucosa of pigs (Fiesel, Gessner, Most, & Eder, ).…”
Section: Discussionmentioning
confidence: 99%
“…Asadishad, Hidalgo, and Tufenkji (2012) discovered that a pomegranate rind extract and fractions with a molecular weight between 1000 and 3000 kDa strongly inhibited flagellin gene expression on motility of uropathogenic E. coli strain CFT073, suggesting that they might be therapeutically beneficial in the treatment and prevention of uncomplicated urinary tract infections. It has also been found by Zhong et al (2014) that polyphenol extracts from pomegranates protected against inflammation and increased the survival rate of chickens challenged with avian pathogenic E. coli that cause inflammation in organs called colibacillosis, suggesting the potential of the extracts as an alternative medicine for the prevention or treatment of avian colibacillosis. Pagliarulo et al (2016) reported that both pomegranate aril and peel extracts containing multiple bioactive molecules (anthocyanins, catechins, tannins, gallic and ellagic acids) inhibited the bacterial growth of two clinical isolates of E. coli and Staphylococcus aureus that are involved in foodborne illness.…”
Section: Introductionmentioning
confidence: 99%
“…In inflammatory processes of organ tissues, endothelial cells were exposed to various stimuli, including E. coli, inflammatory cytokines, and activated (Molema, 2010), then followed by the increase of E-selectin, ICAM-1 and VCAM-1. For example, E. coli in ovo administration stimulated the expression of ICAM-1 and VCAM-1 in 35-day old chicken ileum intestinal tissue (Zhong et al, 2014), and kidneys in pig (Thorgersen et al, 2013). But APS had a preventive effect against endothelial dysfunction by inhibiting the expression of ICAM-1 and VCAM-1, improving endothelial survival (Zhu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…After binding LPS, TLR4 and its downstream NF-κB are activated, subsequently activated NF-κB translocates into the nucleus to regulate target gene expression (Faure et al, 2000). For example, avian pathogenic E. coli challenge activated TLR4 and NF-κB and stimulated the expression of ICAM-1, VCAM-1, TNF-α and IL-1β in 21-day old chicken ileum intestinal tissue (Zhong et al, 2014). APS inhibited the increase in the expression levels of TLR4 and NF-κB in 35-day old broilers jejunal mucosa (Liu et al, 2015) and the translocation of NF-κB in murine (Lu et al, 2016) with LPS-induced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation